Existence of Four Solutions of Some Nonlinear Hamiltonian System. (14th January 2008) - Jung, Tacksun; Choi, Q-Heung
Abstract : We show the existence of four2 π -periodic solutions of the nonlinear Hamiltonian system with some conditions. We prove this problem by investigating the geometry of the sublevels of the functional and two pairs of sphere-torus variational linking inequalities of the functional and applying the critical point theory induced from the limit relative category.